PENGARUH SKEPTISISME PROFESIONAL, INDEPENDENSI, INTEGRITAS, SERTA KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI SURABAYA - DARMAWAN SANTOSO, RIZKY (Jurnal Akuntansi AKUNESA, 2016)
The purpose of this study is to determine the influence of professional skepticism, the independence, integrity and competence of auditors againts audit quality. As for the object under study is the auditor who works in the public accounting firm of Surabaya. The study was conducted using primary data in the form of a questionnaire. The population of this research that all auditors who worked on KAP in Surabaya, while the sample was selected using purposive sampling by taking 120 respondents. The study was conducted with a quantitative approach. Analysis of data using multiple linear regression analysis. The results of research by the author shows that the professional skepticism, independence, integrity and competence of auditors has a positive significant effect on audit quality. Simultaneously entire variable that are professional skepticism, independence, integrity and competence of auditors has a positive and significant effect on audit quality.   Keywords: Audit Quality, Professional Skepticism, Independence, Integrity, Competence.